Clinical Pharmacokinetic Evaluation of Optimized Liquisolid Tablets as a Potential Therapy for Male Sexual Dysfunction - Fayez O. Alotaibi; Nabil A. Alhakamy; Abdelsattar M. Omar; Khalid M. El-Say (MDPI AG, 2020)
The study aimed at developing a liquisolid tablet (LST) containing tadalafil (TDL) and dapoxetine (DPX) with improved bioavailability as a potential therapy for male sexual dysfunction. A mixture of nonvolatile solvents, namely PEG 200 and Labrasol®, was utilized to prepare LSTs that were assessed for their quality characteristics. The Box-Behnken design (BBD) was employed to statistically explore the effect of the formulation factors on the quality attributes of LSTs. Furthermore, an in vivo pharmacokinetic study was carried out for the optimized LST in comparison with the marketed tablets on healthy human volunteers. The optimized LST revealed acceptable quality limits with enhanced dissolution for both APIs. The pharmacokinetic parameters after oral administration of the optimized LST indicated that the Cmax of TDL in LSTs was 122.61 ng/mL within 2h compared to the marketed tablets, which reached 91.72 ng/mL after 3 h, indicating the faster onset of action. The AUC was improved for TDL in LST (4484.953 vs. 2994.611 ng/mL∙h in the marketed tablet) and DPX in LST (919.633 vs. 794.699 ng/mL∙h in the marketed tablet). This enhancement in bioavailability potentially minimizes the associated side effects and improves the treatment of male sexual dysfunction, particularly for diabetic patients.